(untitled) (Scientific journal of the Fergana State University, 2024)
The significance of Fritillaria sewerzowii in folk medicine and its use, i.e. the order of application, is explained. Scientific sources and previous studies related to the study of the chemical composition of the plant are presented. The process of extraction of Fritillaria sewerzowii with water and devices for studying the composition of macro- and microelements of the resulting aqueous extract, the principles of their operation and results are presented. A comparative analysis of the composition of macro- and microelements in the initial sample of the onion plant and the last sample after extraction with water is also considered